Monitoring of Wastewater Quality from Laundry and Car Wash Industries at Batu Pahat, Johor - Abu Bakar, A.; H. Hashim, N.; ., . (International Journal of Engineering & Technology, 2019)
The complexity of environmental chemical exposure become a major concern because an essential objective of the global research effort is to improve life quality feature. Currently, environmental monitoring has become even more critical as human population increase, with the increasing strains on the environment. The unwanted synthetic compounds that presence from grey water in natural water was lead a toxic effect on ecosystems thus may lead to changes in biodiversity. This paper aims to discuss the studies of characterization in the environmental water sample from greywater which were laundry wastewater and car wash wastewater in the area surrounding Batu Pahat, Johor, Malaysia. The samples were directly brought to the laboratory for analysis and the content of grey water quality was characterized by using physicochemical analyses including pH, conductivity, suspended solids, chemical oxygen demand (COD), anionic surfactants (AS), oil and grease, sulfate, chloride, nitrate, and nitrite. All parameters were tested according to the standard method (APHA 2012). The result of this studies showed that the concentrations of AS by using methylene blue active substances (MBAS) were higher in laundry wastewater compared to car wash wastewater which was maximum at 105.0 mg/L. While the COD for car wash wastewater was maximum at 531.1 mg/L which was higher than laundry wastewater. Some of the characterizations indicated high values for many parameters and there is the need for specific treatment prior to discharge to before it has been directly discharged to the drainage.Â Â